Analisis Kuantitatif Mangan (Mn) dan Besi (Fe) Menggunakan Spektrofotometri Serapan Atom pada Eucheuma cottonii serta Penilaian Kualitas Air Laut di Pantai Pokko - Rifdah Mawaddah Rustam; Abd Wahid Wahab; Syarifuddin Liong; Indah Raya; Herlina Rasyid (Chemistry Department, 2026)
This study aims to determine the concentrations of the heavy metals manganese (Mn) and iron (Fe) in seawater and in the tissue of the seaweed Eucheuma cottonii, collected from the coastal waters of Pokko Beach, Takalar Regency, South Sulawesi. Sampling was conducted at four stations selected based on the level of human activity in the surrounding coastal area, and was carried out during two sampling periods. The concentrations of the metals were analyzed using the atomic absorption spectrophotometry (AAS) method. The results showed that Mn concentrations in seawater during the first sampling were 0.52, 0.37, 0.06, and 0.03 mg/L, increasing in the second sampling to 1.14, 1.09, 1.77, and 0.60 mg/L. In seaweed tissue, Mn concentrations during the first sampling were recorded at 126.22, 41.20, 28.78, and 9.89 mg/kg, and increased to 83.41, 56.88, 117.25, and 208.10 mg/kg in the second sampling. For Fe, concentrations in seawater during the first sampling were 2.00, 2.13, 1.68, and 1.01 mg/L, and increased sharply in the second sampling to 14.48, 33.45, 3.39, and 10.10 mg/L. In seaweed tissue, Fe concentrations were 292.56, 5,714.25, 200.46, and 395.78 mg/kg in the first sampling, and 1,615.66, 585.13, 489.98, and 1,007.38 mg/kg in the second. The variation in heavy metal concentrations between stations and sampling periods was influenced by several factors, including physical conditions of the water (such as temperature, pH, and salinity), ocean currents, and human activities near the sampling sites, particularly around docks and seaweed farming areas. These findings indicate that anthropogenic activities significantly contribute to the increased contamination of heavy metals in marine waters and biota.